Filmmakers and financing : business plans for independents - Levison, Louise (Focal Press, 2010)
The first, most crucial step in making a film is finding the funds to do it. Let Louise Levison, who wrote the innovative business plan for "The Blair Witch Project," show you how. This unique guide teaches you not only how to create a business plan, but also how to avoid common business plan mistakes, so that you can attract and secure an investor. In jargon-free terms, the author leads you through every step. Each chapter concentrates on a different section of the business plan, including the industry, marketing, financing, and distribution. Large format films, new media and shorts are also discussed. The included companion web site features supplementary exercises and spreadsheets so that you get comfortable crunching the numbers--no math degree required! The sixth edition contains completely revised and updated industry data along with updated information on distribution including online and foreign markets. Plus, new interviews and case studies with filmmakers will show you real-world examples of equity investors and markets. * Includes a companion web site with sample business plans, forms, spreadsheets, and hands-on exercises * Learn from real-world examples with new interviews and case studies. * Rock-solid guidance on how to develop a successful business plans for features, shorts, documentaries and more